The effect of topical oatmeal (Avena sativa) on hydration-related skin disorders: A systematic review - Sugondo, Karenina Novani; Hermawan, Melyawati (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: In recent years, interest in developing cosmetics and beauty products based on natural ingredients has increased. The addition of herbal extracts to products could improve the effectiveness of therapy. One of the natural ingredients that can be found is oatmeal. Oatmeal has been used for a long time and has been approved by the U.S. Food and Drug Administration as a skin protective agent since 2003. This study aims to systematically review the literature to determine the effect of topical oatmeal (Avena sativa) on hydration-related skin disorders. Methods: A total of 9,538 studies were found in the database sources such as PubMed, ProQuest, Clinical Key, Cochrane, Clinical Trial, and EBSCO. The inclusion criteria were all randomized controlled trials published from 2010 to 2020 that evaluated the effect of oatmeal-contained moisturizers on hydration-related skin disorders. The risk of bias was assessed using the Cochrane risk-of-bias tool for randomized trials (RoB2). Result: A total of five studies were included in this systematic review. These studies were published in 2015-2020. The forms of oatmeal in the five studies differ, such as emollient, lotion, and cream extracts. The skin disorders in the literature also vary, such as chronic pruritus, uremic pruritus, atopic dermatitis, irritant hand eczema, and dry skin. Conclusion: Although the form of oatmeal, skin disorders, and age range in each literature differ, it can be concluded that an oatmeal-contained moisturizer could improve the clinical assessment and the objective measurement of various hydration-related skin conditions.